Diabetic kidney disease versus non‐diabetic kidney disease in type 2 diabetic patients on dialysis: An observational cohort. Issue 4 (30th April 2022) - Delautre, Arnaud; Hannedouche, Thierry; Couchoud, Cécile; Guiserix, José; Cerasuolo, Damiano; Chantrel, François; Martzloff, Jonas; Keller, Nicolas; Krummel, Thierry; ,
Abstract: Background: All chronic kidney diseases in diabetic patients are not diabetic kidney diseases. The objective was to compare the clinical characteristics, survival and access to transplantation in diabetic patients starting dialysis and classified either as diabetic kidney disease (DKD) or non‐diabetic kidney disease in diabetic patients (NDKD). Methods: We used the nationwide French REIN registry to analyse baseline clinical characteristics at dialysis inception and outcomes defined as kidney transplantation, deaths and their causes. The probability of death or transplantation was analysed using a multivariate Cox model and the Fine and Gray competing for risk model (sdHT). Results: We included 65, 136 patients from January 2009 to December 2015 with a median follow‐up of 31 months. The cumulative incidence of kidney transplantation over eight years was 46.9% (44.8–48.9) in non‐diabetic patients (ND), higher than the 19.3% (17.5–21.2) in the DKD group and 22.2% (18.4–26.7) in the NDKD group. The risk of death was significantly higher in the NDKD group than in the DKD group, even after accounting for the competing risk of transplantation (NDKD/sdHR 1.22; 95%CI 1.18–1.27; p < 0.005 vs. DKD/sdHR 1.12; 95%CI 1.08–1.16; p < 0.005 with adjustment for age, sex, major adverse cardiovascular events, cancer and chronic respiratory failure, compared to ND). Conclusions: In diabetic patients starting dialysis, patients in the DKD group had reduced access to kidney transplantation. NDKD patients had a higher risk of mortality than DKD. The distinction between DKD and NDKD should be accounted for in the plan of care of diabetic patients starting dialysis. Abstract : What is already known about this subject? Diabetes is the leading cause of end‐stage kidney disease throughout the world. All chronic kidney diseases in diabetics are not diabetic kidney diseases (about 25%). There are few and conflicting data on the prognosis significance of this distinction. What this study adds: We found marked clinical differences between DKD and NDKD groups: more vascular‐related complications, more insulin treatment and more disability in DKD, more cancer, liver diseases and heart rhythm disorders in NDKD patients. Survival was better overall in patients in the DKD versus the NDKD group. Some patients in the NDKD group had more access to kidney transplantation, suggesting heterogeneity in this group. Some clinical factors were found to be associated with reduced access to kidney transplantation, including insulin treatment and congestive heart failure. What impact this may have on practice or policy?. The different outcomes should be accounted for in the plan of care of diabetic patients starting dialysis, especially when planning transplantation, and question a role for expanding indications of kidney biopsies to classify subgroups of diabetic people more accurately.